Efficacy of 5% permethrin-2% fusidic acid cream compared to 5% permethrin-placebo in the treatment of impetiginized scabies - Aninda Marina; Sri Linuwih Menaldi; Endi Novianto; Sandra Widaty (Journal of Infection in Developing Countries)
Introduction: Scabies is caused by Sarcoptes scabiei var hominis, often causing secondary bacterial infections, especially by Streptococcus pyogenes and Staphylococcus aureus. Permethrin 5% cream is the first-line of treatment that is recommended, combined with Fusidic acid 2% cream as the first-line topical antibiotic. We investigated the efficacy of a combination of permethrin 5% cream and fusidic acid 2% cream for the treatment of impetiginized scabies.